Status Migrainosus with Lymphocytic Pleocytosis: A Case Report - Bancalari-Benavides, Ernesto (2021)
A 40-year-old man, with a history of migraine, experienced a left occipital headache, tinnitus and photopsias. He was treated with analgesics at the emergency room with partial relief during 3 consecutive visits during the week prior to admission. At admission, general physical exam was normal as was the neurological examination. A lumbar puncture (LP) was performed, showing no blood cells but 100 mononuclear cells with normal protein and glucose levels. Cerebrospinal fluid (CSF) microbiological and virologic tests and brain imaging studies were not contributory. The pain was controlled after a trigeminal nerve block. Five days after admission and with the status migrainosus resolved, a second LP was performed which was reported as normal with resolution of the pleocytosis. Recognition of transitory CSF pleocytosis in the context of an acute migraine episode could serve to avoid unnecessary investigations and misuse of clinical resources when not clinically indicated.